(untitled) (Bangladesh Journal of Medical Science, 2012)
Aim: To evaluate the performance of visual inspection of acetic acid (VIA) in the detection of precancerous and early cancerous lesions of cervix. Materials and methods: Total 5593 eligible women who randomly came to the Gyenae out patient department (OPD) of RMCH (Rajshahi Medical College Hospital) were examined by VIA. Detection of well defined, opaque, acetowhite lesions close to the squamocolumner junction or in transitional zone or dense acetowhitening of ulceroproliferative growth on the cervix constituted a positive VIA. Those who had abnormal results in screening test & those who had clinically suspicious lesions were sent for colposcopic evaluation (n= 442) & directed biopsy were taken from colposcopically suspected areas (n=214). The final diagnosis was based on histology. Results: Out of 5593 patients, 442 (7.20%) were VIA positive. 442 patients were colposcopically evaluated .Among them, 228 (51.58%) were normal and 202(45.70%) had different stages of cervical intraepithelial lesions (CIN) and 12 ( 2.71 % ) had carcinoma of cervix. Out of 214 patients biopsied, 23.36 % patients had a final diagnosis of CIN lesions, 5 (2.33%) had carcinoma in-situ & 17 cases (7.94%) had invasive carcinoma. Besides to find out the predictable factors of cervical lesions data have been collected from VIA positive patients regarding age of first coitus and first delivery, history of extra marital exposure and STI, use of contraceptive methods and family history of cancer. Age of first coitus between 12 to 15 years and 16 to 20 years were observed among 203 (46 %) and 40 % (177) women respectively. More than half of the patients (62%) were experienced with their first delivery within the age 15-20 years which was below 15 years of 12 % (53) patients. Fifty four percent patients used OCP and barrier methods used were only 10 %. Family history of cancer was observed among 09 % women. 58% patients were belonged to lower middle class and upper group were only 9% (table 1) Conclusion: In our study detection of different grades of intraepithelial lesions (CIN-I, CIN-II, CIN-III, invasive carcinoma) of cervix by VIA was comparable to that of colposcopy. So VIA is suitable for detection of precursor lesions of cervical cancer in low resource settings and also for diagnosis, follow up treatment and epidemiological studies of cervical cancer. Key words: Visual inspection; VIA; cervical carcinoma; colposcopy; screening; epidemiological studies. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9494 BJMS 2011; 10 (4): 240-244